Synthetic analogs of strigolactones and their applications - Faizan, Mohammad; Karabulut, Fadime; Fahad, Shah (Elsevier, 2024)
Strigolactones (SLs), a class of carotenoid-derived plant hormones, were primarily discovered as an “ecological indicator” for parasitic seed germination and establishment of symbiotic relationship between plants and useful microbes. It is a germination stimulant for seeds of parasitic weeds, are the branching feature of arbuscular mycorrhizal fungi and repressor for bud outgrowth and shoot branching. Ensuing characterizations have explained their purposeful roles in diverse developmental practices, including root development, shoot branching, reproductive development, and leaf senescence. SLs have newly drained much consideration due to their vital roles in the regulation of several physiological and molecular processes during the adjustment of plants to abiotic constrains. Thus, the role of synthetic analogs of SLs in plants becomes an important area of research. This chapter summarizes the current knowledge of synthetic analogs of SLs including their applications in plants. © 2024 Elsevier Inc. All rights reserved.
Keywords: Arbuscular mycorrhizal fungi; Physiological processes; Seed germination; Shoot branching; Strigolactones